A semi-analytical model for methane transport and oxidation in a soil cover. (June 2021) - Wang, Qiao; Zuo, Xinru; Fei, Shuangke; Xie, Haijian; Qiu, Zhanhong; Sun, Zhilin
Abstract: An analytical model for methane and oxygen transport through a single soil cover considering diffusion, advection, and oxidation was developed. The results obtained by the analytical model agree well with those obtained by the numerical model and the column tests. Dimensionless analysis indicates that methane emission flux is more sensitive to the variation of Pe and Da numbers when advection dominates methane transport ( Pe  ≥ 1) and oxidation dominants methane transport ( Da  ≥ 10), respectively. It also indicates that landfill gas pressure build-up will decrease the amount of oxygen migrating into the soil. The methane emission flux for the case with Sr  = 0.2 is 5.30 and 200 times greater than the cases with Sr  = 0.5 and 0.8, respectively. The methane removal efficiency for the case with Sr  = 0.8 is 1.25 and 1.58 times greater than the cases with Sr  = 0.5 and 0.2, respectively. With the increase of Sr (soil moisture content), methane oxidation rate increases, and diffusion coefficients and advection rates decrease. The methane removal efficiency was increased because more amount of methane was stuck and oxidized in the soil.